Enhanced Light Harvesting in Dye-Sensitized Solar Cell Using External Lightguide - Chi-Hui Chien; Ming-Lang Tsai; Chi-Chang Hsieh; Yan-Huei Li (International Journal of Photoenergy)
An external lightguide (EL) for enhancing the light-harvesting efficiency of dye-sensitized solar cells (DSSCs) was designed and developed. The EL attached to the exterior of a DSSC photoelectrode directed light on a dye-covered nanoporous TiO2 film (D-NTF) of the photoelectrode. Experimental tests confirmed that the EL increased the light-harvesting efficiency of a DSSC with an active area of 0.25 cm2 by 30.69%. Photocurrent density and the power conversion efficiency were also increased by 38.12% and 25.09%, respectively.